1993
DOI: 10.1017/s0022112093000382
|View full text |Cite
|
Sign up to set email alerts
|

On some kinematic versus dynamic properties of homogeneous turbulence

Abstract: A comparison is made between a number of properties of a quasi-homogeneous isotropic turbulent field obtained from a direct numerical simulation of the Navier–Stokes equation and its random counterpart with the same energy spectrum. It is demonstrated that some effects in a real flow have a considerable contribution of a kinematic nature (e.g. reduction of nonlinearity), while others are mostly dynamical (e.g. alignment between vorticity and eigenvectors of the rate of strain).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 11 publications
7
42
0
Order By: Relevance
“…2b, characterizing the distribution of alignment between the vortex stretching and the vorticity vectors. The curves for DNS and random data are similar to those presented by Shtilman et al (1993), who noted that the alignment between these vectors is also a dynamic characteristic of turbulence, and its asymmetry is associated with positive enstrophy generation. Once again the peaks are less pronounced in the HATS dataset.…”
Section: B Atmospheric Stability and Resolved Velocity Gradient Strusupporting
confidence: 79%
“…2b, characterizing the distribution of alignment between the vortex stretching and the vorticity vectors. The curves for DNS and random data are similar to those presented by Shtilman et al (1993), who noted that the alignment between these vectors is also a dynamic characteristic of turbulence, and its asymmetry is associated with positive enstrophy generation. Once again the peaks are less pronounced in the HATS dataset.…”
Section: B Atmospheric Stability and Resolved Velocity Gradient Strusupporting
confidence: 79%
“…An important case where the origin of a dynamical effect is unclear is the alignment of the middle eigenvector (associated with the middle eigenvalue) of the rate of strain tensor with the vorticity. This alignment is not seen in Gaussian or random turbulence (Shtilman et al 1992). Ashurst et al (1987) and Vincent & Meneguzzi (1991) have observed such an alignment in Direct Numerical Simulations and believed it to arise from poorly understood nonlinear effects.…”
Section: Structures and Dynamics In Distorted Turbulencementioning
confidence: 95%
“…In the case of stretching of vorticity, one always has ω ω ω ≡ 0 which means that vorticity vector is unaffected by the antisymmetric part of the velocity gradient tensor. It was argued in [8] that in the context of 3D flows the angle γ ω = ∠(Dω Dω Dω, ω ω ω) between vorticity and the so called 'vortex stretching' vector has particularly interesting properties. In our case the equivalent would be γ ∇ω = ∠(D D D∇ ∇ ∇ω ω ω, ∇ ∇ ∇ω ω ω).…”
Section: Characterization Of Geometrical Alignmentsmentioning
confidence: 99%